Pesan dakwah dalam KH. Ahmad Mustofa Bisri Tentang Pembakaran Bendera Tauhid Di Youtube (Analisis Semiotika Charles Sander Pierce) - Moch Nurcholis Majid (Program Studi Komunikasi dan Penyiaran Islam Fakultas Dakwah IAI Uluwiyah Mojokerto, 2021)
research is to know the content of the message and the meaning of the message sign of da'wah in a lecture on Youtube: based on the message structure and theory of semiotic analysis of the Charles S. Peirce model. To identify these problems in depth and depth, the researchers used qualitative research methods using the semiotic analysis of Charles S. Peirce's model which is non-environmental. This study resulted in the findings of the Da'wah Message in Youtube lectures: on the message of da'wah in KH Mustofa Bisri's lecture on Youtube with the title Gus Mus's Advice for Indonesian Muslims (KH Mustofa Bisri's Message related to the HTI Airport Polemic or the Tawhid Flag), the contents of the message conveyed in the video The meaning of the message contained in Gus Mus's lecture related to HTI news shows the values ​​of the da'wah message in the form of faith and morality. The next recommendation is to conduct in-depth research with data on the perception of listeners while using quantitative methods so that there are decent results.message of da'wah